Projeto memória do CET: relato de experiência - Fernandes, Flávia Sperandio [UNESP]; Machado, João Guilherme de Camargo Ferraz [UNESP]; Sabbag, Deise Maria Antonio (Universidade Estadual Paulista (Unesp), 2015)
The CET Memory project aims to encourage the creation and maintenance of a collection of the Campus Experimental of Tupa, from recording, organization, expansion, scanning and storage of documents, photographs and testimonies recorded / filmed, promoting the memory of the Campus. This project has an ongoing character characterized by activities developed and distributed throughout the year. So far, they have been scanned and archived 503 newspaper reports about the Campus, 9128 photos since its creation, implementation and consolidation, and seven videos. They were also held two exposures with the material of the collection.

O projeto Memória do CET tem como objetivo fomentar a criação e manutenção de um acervo sobre o Campus Experimental de Tupã, a partir do registro, organização, ampliação, digitalização e a conservação de documentos, fotografias e depoimentos gravados/filmados, que promovam a memória do Campus. Esse projeto possui um caráter contínuo caracterizado por atividades desenvolvidas e distribuídas ao longo do ano. Até o momento, foram digitalizadas e arquivadas 503 matérias de jornais sobre o Campus, 9128 fotos desde sua criação, implantação e consolidação, e sete vídeos. Também foram realizadas duas exposições com o material do acervo.
Keywords: Documentation; Memory; History; Campus Experimental of Tupa; Documentação; Memória; História; Campus Experimental de Tupã